2019
DOI: 10.7566/jpsj.88.081003
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization and Decay of Magnetic Excitations in Two-Dimensional Triangular Lattice Antiferromagnets

Abstract: Elementary quasiparticles in solids such as phonons and magnons occasionally have nontrivial interactions between them, as well as among themselves. As a result, their energy eigenvalues are renormalized, the quasiparticles spontaneously decay into a multi-particle continuum state, or they are hybridized with each other when their energies are close. As discussed in this review, such anomalous features can appear dominantly in quantum magnets but are not, a priori, negligible for magnetic systems with larger s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 171 publications
(272 reference statements)
0
8
0
Order By: Relevance
“…In the latter case, this many body effect is typically enhanced near quantum critical points that signal a continuous quantum phase transition between two different phases. For these reasons, spontaneous magnon decay has been studied both theoretically and experimentally in a growing number of lattice geometries and model systems with large quantum fluctuations [9,10]. Studies in triangular lattice materials have revealed that the strong decay processes are accompanied by a significant renormalization of the overall spectra [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, this many body effect is typically enhanced near quantum critical points that signal a continuous quantum phase transition between two different phases. For these reasons, spontaneous magnon decay has been studied both theoretically and experimentally in a growing number of lattice geometries and model systems with large quantum fluctuations [9,10]. Studies in triangular lattice materials have revealed that the strong decay processes are accompanied by a significant renormalization of the overall spectra [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Short-wavelength magnetic excitations in spin- 1 2 Heisenberg antiferromagnets (HAFs) have attracted much attention recently. This interest has been stimulated by recent analytical, 1-3 numerical, [4][5][6][7][8] and experimental [9][10][11][12][13] works which have appeared, in particular, due to the rapid progress in computer power, numerical methods, and experimental facilities. Then, spin excitations are considered now as one of the promising candidates to provide a "glue" for high temperature superconductivity with an important role of short-wavelength excitations.…”
Section: Introductionmentioning
confidence: 99%
“…One of the strongest signatures of collective quantum behavior is the spontaneous quasiparticle decay in interacting bosonic systems, as observed in super-fluids (1-3) and quantum magnets (4)(5)(6)(7)(8). In the latter case, spontaneous magnon decay has been studied in a growing number of lattice geometries and model systems where large quantum fluctuations enhance this many body effect (9,10). A key finding of these studies is that the strong decay process is accompanied by a significant renormalization of the overall spectrum (11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%